Some Aspects of Development of Private International Law in the CIS Countries - Islambek Rustambekov (LeXonomica, 2020)
Globalization, development of the states and society and their rapprochement makes the issues of regulation of relation with a foreign element more urgent, and in particular private international law becomes relevant. In this aspect, states are aimed in unification and harmonization of norms of private international law and mostly within regional associations. This article traces these issues within the Community of Independent States (CIS). The CIS countries are trying to analyze and use the international experience, in particular similar experiences of the EU. The EU experience is acutely important in view of the development of Eurasian Economic Union in which more States are trying to become a member. This article traces the development and rapprochement of the private international law in the EU and the CIS countries, and analyzes international agreements of the States which are aimed to unify private international law and regulate such relations around the States. The article reflects upon and provides some basic perspectives regarding further regional harmonization and unification of private international law in the CIS.